2021
DOI: 10.1192/j.eurpsy.2021.1409
|View full text |Cite
|
Sign up to set email alerts
|

Performance on verbal fluency in late-onset schizophrenia is more preserved than in early-onset schizophrenia

Abstract: IntroductionAccording to the literature, cognition may be more preserved in late-onset schizophrenia (LOS) compared to early-onset schizophrenia (EOS), but data are limited.ObjectivesTo compare performance on cognitive tests in LOS and EOS.MethodsLOS patients (n=14, mean age 58.1±8.2, 13 females, illness duration 1.07±1.5 years) and age-comparable controls (n=17, mean age 55.3±7.8, 12 females), EOS patients (n=25, mean age 20.7±3.9, 25 males, illness duration 0.75±0.62 years) and age-comparable controls (n=15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In the present study, it was found that EO patients had poorer cognitive functioning than non-EO patients, especially in the visuospatial/constructional and language domains. Our findings align with previous research that found people with EO schizophrenia had more severe impairments in various cognitive functions, such as verbal fluency and verbal memory [40,41]. Furthermore, our results suggest that EO patients have more serious negative symptoms than non-EO patients, which is also in line with the results of some earlier research [42,43].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was found that EO patients had poorer cognitive functioning than non-EO patients, especially in the visuospatial/constructional and language domains. Our findings align with previous research that found people with EO schizophrenia had more severe impairments in various cognitive functions, such as verbal fluency and verbal memory [40,41]. Furthermore, our results suggest that EO patients have more serious negative symptoms than non-EO patients, which is also in line with the results of some earlier research [42,43].…”
Section: Discussionsupporting
confidence: 93%